Effect of Blanching and Lactobacilus Acidophillus to Pickle Bitter Gourd (Momordica Charantia) Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Bitter gourd is (Momordica charantia) widely cultivated as a vegetable and medicinal herb in Vietnam. Bitter gourd is a highly nutritive plant composed of different benificial compound including bioactive chemicals, vitamins, minerals, antioxidants. Bitter gourd has lot of health benefits with good nutritional value but it is not consumed extensively due to its bitterness, the processing methods improved nutrients. Lactic acid fermentation may be considered as a simple and valuable biotechnology for maintaining and/or improving the safety, nutritional, sensory and shelf life properties of bitter gourd. The objective of this study was to evaluate different aspects affecting to the fermentation of bitter gourd such as concentration of CaCl2, temperature and time for blanching; effect of ratio Lactobacilus acidophillus to the antioxidant, firmness and bitterness of pickle bitter gourd. Results showed that bitter gourd should be blanched in hot water 95oC in 10 seconds with the present of 2.0% CaCl2. Moreover, the fermentation process for pickle Bitter gourd (Momordica charantia) had the best antioxidant by Lactobacilus acidophillus at ratio 1.5 x 108 cells/ml. Blanching and fermentation had significantly affected to antioxidant capacity, bitterness and firmness of pickle bitter gourd (Momordica charantia).Keywords: Bitter gourd, Momordica charantia, Pickle, fermentation, Blanching, Lactobacilus acidophillus, Antioxidant.